Writing a letter to the editor - Peh, W.C.G.; Ng, K.H. (Singapore Medical Assoc, 2010)
A letter to the Editor is a short communication. It can be written on any subject of interest to the journal reader, and is published at the Editor's discretion. Comments on previously published articles are probably the most common reason for writing a letter. A variety of other types of letters exist, depending on individual journal policy. Letters to the Editor should be objective, constructive and purposeful. They should provide new or useful information that merits publication, or additional or alternative viewpoint or experience to a previously published article. Letters should be short and concise, with clear and specific points.